A CiteSpace-based Analysis of Corporate Social Responsibility Research in China - Zhou, Zhiyi (Advances in Social Sciences Research Journal, 2023)
This paper applies CiteSpace, a visualization analysis tool, to analyze the inner relationship among documents collected from “Chinese Social Sciences Citation Index”, to unveil the present situation and future orientation of studies on corporate social responsibility in China.